A Descriptive Perception vs. Achievement Analysis of Continuance Improvement in Malaysian ISO 9001-Certified Smes - Anwar Razali, Khairil; Shaaban, Azizah (International Journal of Engineering and Technology, 2018)
In todayâ€™s competitive market, organizations are required to continuously improve their business processes and maintaining continuous improvement of ISO 9001 benefits. Besides continuous improvement, current literature claims that the common benefits of the ISO 9001 certification are â€œCustomer satisfaction focusâ€, â€œManagement & Reviewâ€, â€œOrganizational performanceâ€ and the factors for TQM implementation (e.g Supplier quality management, Vision and plan statement). The purpose of this paper is to compare the level of perception vs. achievement of factors maintaining continuance improvement for 27 randomly selected Malaysian ISO 9001 certified SMEs as a primary study. Respondents of this study rated organizational performance is the most importance aspect of successful factor of ISO 9001, followed by organizationâ€™s highest level of achievement. This study also finds that the most important construct of TQM implementation is quality system improvement and the highest level of organizationâ€™s TQM implementation achievement is customer relationship. This study also shows that there is a significant difference between companiesâ€™ perception of the level of important and achievement in factors for successful of ISO 9001 and TQM implementations. For practitioners, this study addresses how continuous improvement has evolved and how to maintain benefits from ISO 9001 certifications.Â Keywords: Successful ISO 9001; Continuous improvement; ISO 9001 benefits; ISO 9001 barriers; TQM implementation, Customer SatisfactionIn todayâ€™s competitive market, organizations are required to continuously improve their business processes and maintaining continuous improvement of ISO 9001 benefits. Besides continuous improvement, current literature claims that the common benefits of the ISO 9001 certification are â€œCustomer satisfaction focusâ€, â€œManagement & Reviewâ€, â€œOrganizational performanceâ€ and the factors for TQM implementation (e.g Supplier quality management, Vision and plan statement). The purpose of this paper is to compare the level of perception vs. achievement of factors maintaining continuance improvement for 27 randomly selected Malaysian ISO 9001 certified SMEs as a primary study. Respondents of this study rated organizational performance is the most importance aspect of successful factor of ISO 9001, followed by organizationâ€™s highest level of achievement. This study also finds that the most important construct of TQM implementation is quality system improvement and the highest level of organizationâ€™s TQM implementation achievement is customer relationship. This study also shows that there is a significant difference between companiesâ€™ perception of the level of important and achievement in factors for successful of ISO 9001 and TQM implementations. For practitioners, this study addresses how continuous improvement has evolved and how to maintain benefits from ISO 9001 certifications.Â Â
Keywords: Successful ISO 9001; Continuous improvement; ISO 9001 benefits; ISO 9001 barriers; TQM implementation; Customer Satisfaction